Analysis of impact of intervention rate bank of the Republic of Colombia interest in the stock market index col20 the Colombian stock market 2008-2013 (2013)
This paper has as main purpose to analyze the impact of interest rate intervention by the Bank of the Republic of Colombia in the behavior of stock index COL20. For this, a study should be conducted from the economic and financial theories, and an analysis of the two variables where the resulting impact is measured in COL20 by the interest rates.